Alat Penerjemah Bahasa Isyarat Huruf Hijaiyah Menggunakan Sensor Fleksibel dan Mpu 6050 Berbasis Arduino - Yahya, Dhofirul; Putra, Bayu Charisma; Anam, Khairil; Farkhan, M. (Puslitbang Sinergis Asa Professional, 2024)
In this era of development, communication is important to convey information to avoid misunderstandings. In several community groups, there are people with disabilities, especially speech impairments. People with speech impairments can only communicate using sign language in their daily lives. People with speech impairments learn the Hijaiyah letters as the basis for forming words and sentences in Arabic, guided by Arabic Sign Language. They use sign language to understand what each other says, whereas it would be difficult for normal people to understand. The method that the author used to create a Hijaiyah sign language translation tool was the experimental method and literature review. This translation tool is based on Arduino Nano with display results using a smartphone consisting of an Arduino Nano circuit equipped with a flexible sensor, MPU 6050 sensor, battery and application on the smartphone. For communication needs, a Bluetooth HC 05 series is used. The results of the Hijaiyah letter translator tool will be displayed on the smartphone application. From the experimental results of this research, an accuracy result of 91% was obtained